(untitled) (Intent Research Scientific Journal, 2023)
Since beautiful teeth are important for self-esteem and a sense of comfort, there is a tendency in orthopedic dentistry to use non-metallic restoration materials. Patients want their restorations to be aesthetic, biocompatible, natural-looking and durable.